220k views
5 votes
Simplify the expression. Picture provided. Please help.

Simplify the expression. Picture provided. Please help.-example-1
User Lexikos
by
5.8k points

1 Answer

1 vote

Answer:
(x^(11)y^6)/(9)

Explanation:

Remember the following:

- The Product of powers property:


a^m*a^n=a^(m+n)

- The Quotient of powers property:


(a^m)/(a^n)=a^(m-n)

- And the Negative exponent rule:


(1)/(a)=a^(-1)

Therefore, having the expression
((3x^2y^(-3)))/(27(xy)^(-9)), you can simplify it by applying the properties mentioned before.

Then, you get:


((3x^2y^(-3)))/(27(xy)^(-9))=((3x^2)x^9y^(9))/(27(y)^(3))=(3x^(11)y^6)/(27)=(x^(11)y^6)/(9)

User Alfaplus
by
6.6k points